Geography Syllabus in the Secondary Schools of India: Issues and Challenges - SARFARAZ ALAM (Romanian Review of Geographical Education, 2020)
Constructi ng the syllabus of a school subject coul d be a highly contested exercise given the fact that it must cater for the concerns of competing stakeholders and pressures to incorporate all possible aspects of that discipline. For geography, whose field of study is extremely vast, and its nature is not clearly defined, developing its syllabus is particularly challenging. This paper discusses some key issues concerning the status of the geography syllabus in the secondary schools in India. The central theme of t he paper is built on the study of documenta ry sources, research works, as well as on the survey of schoolteachers and geography experts from some school boards. The paper concludes that the educational value of school geogr aphy can only be realized by inco rpo rating both physical an d human aspects of the Earth in the sylla